دراسـة العلاقــات التشـابكيـة بين قطـاع الزراعـة والقطـاعـات الاقتصـاديـة الأخرى في سـوريـة باسـتخدام التحليل القانوني خلال الفترة (2000 – 2016) - دريباتي, يسيرة; محمود, محمد; اطوز, ملك (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The agricultural sector has an important and vital role in the Syrian economy, through its contribution in supplying inputs to other economic sectors, and its dependence on these sectors to obtain the necessary inputs to accomplish the production process. So, this research aims to study the relationship between agricultural sector and other sectors through their contribution to the GDP by using Canonical correlation analysis in Syria between 2000-2016, to reach the Canonical models represent the studying relationship. Results found, there is a significant relationship between of agricultural sector indicators and other economic sectors expressed in two pair of canonical components. The group of independent variables consists of (plant- agricultural production, capital invested in the agricultural sector - agricultural production requirements - agricultural bank loans - agricultural labor - agricultural export), The group of dependent variables consists of sectoral GDP of (Mining & quarrying and manufacturing, wholesale & retail trade and repair, building and Construction; transport & storage and communications services – finance and insurance and real estate services – Social and personal services, Government services). يتميز القطـاع الزراعي بدوره الهـام والحيوي في الاقتصـاد السـوري من خلال مسـاهمتـه في تأمين مدخلات القطـاعـات الاقتصـاديـة الأخرى، واعتمـاده على هـذه القطـاعـات في الحصـول على المدخـلات اللازمـة لاتمـام الإنتـاج. لذلك يهدف البحـث إلى دراسـة العلاقـة بين مؤشـرات القطـاع الزراعي والقطاعـات الاقتصـاديـة الأخرى من خلال مسـاهمتهـا في تكوين الناتج المحلي الإجمالي في سـوريـة خلال الفترة (2000 – 2016) باسـتخدام التحليل القانوني للوصول إلى المركبـات القانونيـة الممثلـة لهـذه العلاقـة. توصلنـا إلى وجـود علاقـة معنويـة بين مؤشـرات القطـاع الزراعي والقطاعـات الاقتصـاديـة غير القطاع الزراعي يعبر عنهـا بزوجين من المركبـات القانونيـة، بحيث تتكون مجموعـة المتغيرات المسـتقلـة من (الإنتاج النباتي، رأس المـال المسـتثمر في القطـاع الزراعي، مسـتلزمـات الإنتـاج الزراعي، قروض المصرف الزراعي، العمالـة الزراعيـة، الصادرات الزراعية)، ومجموعـة المتغيرات التابعـة من قيمـة الناتج المحلي للقطـاعـات الاقتصـاديـة (الصناعة والتعديبن والمحاجر، تجارة الجملة والتجزئة والاصلاح، البنـاء والتشـييد، خدمـات النقل والتخزين والاتصـالات، خدمـات المـال والتأمين والعقـارات، خدمـات المجتمع والخدمـات الشـخصيـة، الخدمات الحكومية).